2017
DOI: 10.1111/jcmm.13267
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ceramide synthase 2 exacerbates dextran sodium sulphate‐induced colitis in mice due to increased intestinal permeability

Abstract: Ceramides mediate crucial cellular processes including cell death and inflammation and have recently been implicated in inflammatory bowel disease. Ceramides consist of a sphingoid long‐chain base to which fatty acids of various length can be attached. We now investigate the effect of alerting the ceramide acyl chain length on a mouse model of colitis. Ceramide synthase (CerS) 2 null mice, which lack very‐long acyl chain ceramides with concomitant increase of long chain bases and C16‐ceramides, were more susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…with comorbidities is the loss of intestinal permeability barrier triggered by an alteration in TJ expression such as ZO-1 and occludin. 30,[53][54][55][56] The maintenance of the intestinal epithelial barrier mainly depends on the dynamic F I G U R E 1 1 Effect of PEAOXA on neuronal activation and neurotrophic factor after colitis. Immunofluorescence of NeuN in Sham (A), DSS (B), and PEAOXA (C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with comorbidities is the loss of intestinal permeability barrier triggered by an alteration in TJ expression such as ZO-1 and occludin. 30,[53][54][55][56] The maintenance of the intestinal epithelial barrier mainly depends on the dynamic F I G U R E 1 1 Effect of PEAOXA on neuronal activation and neurotrophic factor after colitis. Immunofluorescence of NeuN in Sham (A), DSS (B), and PEAOXA (C).…”
Section: Discussionmentioning
confidence: 99%
“…(mol mass 4.4 and 40 kDa; Sigma) administered by gavage (0.6 g/kg bodyweight in 0.1 mL in PBS) as described previously. 30…”
Section: Evaluation Of Intestinal Barrier Functionmentioning
confidence: 99%
“…46) Previous studies revealed that sphingolipids are involved in IBD including UC. The depletion of SphK-1, 7,25) S1P phosphatase-2 mainly expressed in gut tissues, 9) and sphingomyelin synthase-2 10) prevented DSS-induced colitis in mice, whereas colitis was enhanced in gut-specific conditional S1P lyase knockout mice. 47) The loss of S1P phosphatase-1, 9) ceramide synthase-2, 11) alkaline ceramidase-3, 26) and neutral ceramidase 48) exacerbated DSSinduced colitis in mice.…”
Section: Possible Roles For Prostanoid and Cytokine Levels In Dss-indmentioning
confidence: 96%
“…30) A treatment with DSS changed immune cell homeostasis and inflammation-related gene expression in tissues and individuals, and these changes were different in mice showing modified sphingolipid metabolism. 7,10,12,14,25,44) C1P and/or C1P-regulated cytokines modify the migration of various cells. 14) Changes in immune cell homeostasis, the cytokine balance, and cell migration in DSStreated CerK (−/−) mice need to be examined in more detail in future studies.…”
Section: Possible Roles For Prostanoid and Cytokine Levels In Dss-indmentioning
confidence: 99%
See 1 more Smart Citation